72.3k views
1 vote
Solve the quadratic equation by completing the square. 3x2 - 6x - 4 = 0

User Bruno Gelb
by
5.5k points

2 Answers

3 votes

Answer: is in picture below

Explanation:

Solve the quadratic equation by completing the square. 3x2 - 6x - 4 = 0-example-1
User Edward Minnix
by
5.9k points
4 votes

Answer:

The solutions are


x=1+\sqrt{(7)/(3)}


x=1-\sqrt{(7)/(3)}

Explanation:

we have


3x^(2)-6x-4=0

Group terms that contain the same variable, and move the constant to the opposite side of the equation


3x^(2)-6x=4

Factor the leading coefficient


3(x^(2)-2x)=4

Complete the square. Remember to balance the equation by adding the same constants to each side


3(x^(2)-2x+1)=4+3


3(x^(2)-2x+1)=7

Rewrite as perfect squares


3(x-1)^(2)=7


(x-1)^(2)=(7)/(3)

square root both sides


x-1=(+/-)\sqrt{(7)/(3)}


x=1(+/-)\sqrt{(7)/(3)}


x=1+\sqrt{(7)/(3)}


x=1-\sqrt{(7)/(3)}

User Ramin Afshar
by
5.9k points